Net house evaluation of resistance in rice genotypes against white backed plant hopper, Sogatella furcifera (Horvath) - Rath, P C (ORYZA-An International Journal of Rice, 2018)
Fifty one rice varieties including checks, were evaluated as per Standard Evaluation System for their resistance against white backed plant hopper Sogatella furcifera (Horvath) under net house condition at National Rice Research Institute, Cuttack during 2011 and 2012. Result of the experiment revealed that five varieties i.e. PS3, Satabdi, Radhi, Kalinga 1 and Hazaridhan were found resistant (Score 1) against WBPH during both the year under study and can be used as donor for varietal development programme. Thirteen varieties i.e. Annada, Satyakrishna, Virendra, Sadabahar, Heera, Varsadhan, Jogen, Neela, Khanish, Tara, ASD-16, CSR-4 and PR113 were moderately resistant (Score 3) and thirty one varieties were under susceptible to highly susceptible category (score ï‚³ 5).